Targeting PPARy signaling cascade for the prevention and treatment of prostate cancer - Sikka, S.; Chen, L.; Sethi, G.; Kumar, Alan Prem (Hindawi Publishing Corporation, 2012)
The peroxisome proliferator-activated receptor-gamma (PPARγ) is a member of the hormone-activated nuclear receptor superfamily. PPARγ can be activated by a diverse group of agents, such as endogenous polyunsaturated fatty acids, 15-deoxy- Δ 12,14-prostaglandin J2 (15d-PGJ2), and thiazolidinedione (TZD) drugs. PPARγ induces antiproliferative, antiangiogenic, and prodifferentiation pathways in several tissue types, thus making it a highly useful target for downregulation of carcinogenesis. These TZD-derived novel therapeutic agents, alone or in combination with other anticancer drugs, have translational relevance in fostering effective strategies for cancer treatment. TZDs have been proven for antitumor activity in a wide variety of experimental cancer models, both in vitro and in vivo, by affecting the cell cycle, inducing cell differentiation and apoptosis, as well as by inhibiting tumor angiogenesis. Angiogenesis inhibition mechanisms of TZDs include direct inhibition of endothelial cell proliferation and migration, as well as reduction in tumor cell vascular endothelial growth factor production. In prostate cancer, PPARγ ligands such as troglitazone and 15d-PGJ2 have also shown to inhibit tumor growth. This paper will focus on current discoveries in PPARγ activation, targeting prostate carcinogenesis as well as the role of PPARγ as a possible anticancer therapeutic option. Here, we review PPARγ as an antitumor agent and summarize the antineoplastic effects of PPARγ agonists in prostate cancer.